Still Working in the Shadow of Men? An Analysis of Sex Distribution in Publications and Prizes in Canadian History - Chenier, Elise; Chambers, Lori; Toews, Anne (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
This project was inspired by the Canadian Historical Association’s June 2014 awards ceremony at which the majority of prize winners were men. Why, we wondered, are so few women awarded prizes outside the areas of women’s history, the history of sexuality, and the history of childhood and youth? First, we asked who is working in history? To what degree have departments achieved gender parity in hiring? Do women produce work at a rate proportional to their presence in departments? We collected data in three categories: book reviews, other journal content, and books published between 2004 and 2013. We found that women produce fewer books than do men. Women’s books are less likely to be reviewed than are books written by men and few men review books written by women, a fact with significant implications for both advancement and the inclusion of women in the wider curriculum. Women produce a number of articles proportionate to their presence in the discipline; we suggest that this is because articles require less time of one’s own than do books. It is time to revisit openly and explicitly how academic excellence is determined, and how structural forces produce the sexual inequalities documented here and elsewhere.